A Comparative Analysis of Different Imaging Techniques for Measuring the Neck-Shaft Angle in the Proximal Femur. - Abbas Ali, Sajad; Shammari, Ahmed Z.M.; Augla, Wamieth A.J. (Al-Khwarizmi Engineering Journal, 2026)
Clinical settings have an accurate neck shaft angle (NSA), as it directly affects the diagnosis and treatment of hip-related conditions such as hip dysplasia and osteoarthritis. Variations in the NSA measurement can lead to a difference in the patient's condition during imaging and emphasize the importance of standardized protocols to ensure reliability. Reducing measurement anomalies enables health professionals to improve surgical planning and patient results significantly. A functioning and its impact on clinical applications to evaluate different imaging techniques and software platforms based on correlation coefficients in the class can be used to determine stability and reliability. The primary goal of this research was to identify a valid and reliable necklace measurement method (NSA) using different software and methods. The final results indicate that the 3D method for measuring neck shaft Angle (NSA), primarily using AI-driven automatic measurement Radiographic analysis, is the most effective way to determine the neck shaft angle because it has low radiation doses, low costs, high accuracy, and a simple interface. Technology Using available radiographic images to provide much less radiation risk than calculations Tomography (CT), but often with a high accuracy rate of more than 98%. In addition, it streamlines the Measurement process by reducing human error and variability found in manual methods and campaigns' Clinical availability. Therefore, this computer improves the help of technology in surgical planning and improves the patient's results of total hip arthroplasty with accurate neck shaft measurements (NSA). However, using two-dimensional technology, the EOS 2-D/3-D image system is best suited to Measure the neck shaft angle (NSA), exposure with low radiation, high accuracy, and a user-friendly Interface. This system produces much less radiation than traditional imaging techniques such as CT and the production of detailed 2D and 3D images required for accurate surgical schemes. Its capacity to provide accurate Measurement under increasing clinical efficiency makes it an excellent option for achieving the best results in total hip arthroplasty.